Phenolic composition of jussara (Euterpe edulisMartius) from Minas Gerais and Espírito Santo, Brazil, determined by high performance liquid chromatography coupled to diode array detection and electrospray ionization tandem mass spectrometry (HPLC-DAD-ESI-MS) - Carolina Tatagiba da Rocha Dadalto; Isidro Hermosín-Gutiérrez; José Pérez-Navarro; Rosa Maria Ojeda-Amador; Sergio Gómez-Alonso; Paulo César Stringheta; Daniele de Almeida Paula; Marcos Roberto Moacir Ribeiro Pinto; Afonso Mota Ramos (Ciência Rural, 2022)
ABSTRACT: This research assessed the phenolic composition of Jussara pulp from the Brazilian states of Minas Gerais (MG) and Espírito Santo (ES) using HPLC-DAD-MS/MS. Seventeen anthocyanins were detected in fruits, derived from cyanidin, pelargonidin and peonidin. Among the non-anthocyanic phenolic compounds, flavonols (kaempferol, quercetin and isorhamnetin derivatives), flavan-3-ols (catechin, epicatechin, B-type procyanidins and unknown dimers) and resveratrol in its glycosylated form have been identified. Catechin (32.41-60.56 mg 100g-1) and epicatechin (18.86-40.92 mg 100g-1) were the main flavan-3-ols present in the fruits. The samples showed small concentrations of resveratrol glycosides (0.02-0.91 mg 100g-1). The analytical methodology used (HPLC-DAD-ESI-MS/MS) permitted the identification of newly reported compounds in this fruit.